ESTUDO DOS ASPECTOS CLÍNICOS E RADIOGRÁFICOS DOS TERCEIROS MOLARES EM ESTUDANTES DE UMA ESCOLA PÚBLICA DE SÃO LUIS (MA) - Costa, Maria Aparecida (2007)
Third molars present very peculiar characteristics with respect to eruption, inclusion and complications that require more detailed clinical and x-ray evaluation as to better define the diagnosis and treatment strategies when needed. This study aims at investigating third molars clinical and x-ray aspects concerning inclusion, agenesis, complications and anatomic positions in a both sexes population of 155 students ranging from 18 to 21 years old, treated from November, 2006 to May, 2007, at the technological education Federal Centre of Maranhão State. The presence/absence of third molars was verified through clinical and x-rays check ups. Teeth that presented complete root formation were classified into different inclusion states based upon Winter, and Pell Gregory classification. Complications and pathologies concerning these teeth were also recorded. From that 155 student s population, 531 third molars were present and 89 absent. From those 531 present, 462 were evaluated with respect to the inclusion and the proposed classification, once they presented total root formation. Results showed that 51,7% of those teeth were under different inclusion states, in which the majority was partially or semi-included (84,1%) and 15,9% presented total inclusion. According to Winter and Pell Gregory, the most frequent positions were the vertical (70,1%), followed by the mesial (19%), the distal (7,8%) and horizontal (2,8%); others (0,3%) were at the positions A (54,5%); B (38,7%) and C (6,7%), and belonged to the classes I (62,3%), II (35,1%) and III (2,5%). Congenital toothless situation was rather frequent in this population reaching 14,4%. Pathological alterations and sintomatoly associated with this condition such as pain and caries at the adjacent teeth distal portion were observed. Most frequent positions were the Vertical, Class I and position A.